Examining factors influencing SNS news consumption among university students in Somalia : a modified motivational model - Ahmed, Ismail Sheikh Yusuf (Kulliyyah of Islamic Revealed Knowledge, International Islamic University Malaysia, 2018)
News consumption through social networking sites (SNS) is still in a stage of infancy. Scholars have argued that the SNS platforms are no longer used for entertainment alone. They are also used for instrumental and purposeful activities such as learning, business and news consumption, among others. Past studies and reports have established that SNS platforms such as Facebook and Twitter are used as news sources for the public in numerous countries. Even though many studies and reports on SNS news consumption are documented, it was observed that theory-based research on SNS news consumption is not only in its infancy stage but is meagre. Most past research on this subject was guided by the uses and gratifications (U&G) approach, whose explanatory power is limited. Moreover, the majority of prior studies on the subject are conducted in advanced nations such as the United States of America, the United Kingdom and Australia. Little is known about SNS news consumption patterns in less developed nations or about the contributing factors. Consequently, this study examines the utility of an integrated model in explaining news consumption through SNS platforms among university students. It employs the motivational model (MM) as the main theoretical framework and integrates it with additional elements derived from the U&G approach and the theory of reasoned action (TRA). Therefore, this study proposes an integrated model to determine the factors that contribute to SNS news consumption among university students. The data were collected from two leading universities in Banadir region in Somalia, using quota sampling of gender, faculty and university as the main strata. The data were analysed using statistical softwares such as the SPSS programme and partial least squares of structural equation modelling (PLS-SEM). The SPSS programme was used for reporting descriptive statistics, exploratory factor analysis, and reliability tests, and the PLS-SEM with SmartPLS software was employed to validate and test the hypothesized conceptual model. The study's findings indicate that the subjective norms positively predicted perceived usefulness (PU, β = 0.259, t = 4.683, p = .000), perceived enjoyment (PE, β = 0.383, t = 5.778, p = .000), attitude (ATT, β = 0.463, t = 8.433, p = .000), continuous intention (ATT, β = 0.249, t = 3.037, p = .002), motives for instrumental news use (MIN, β = 0.542, t = 10.741, p = .000) and motives for ritualized news use (MRN, β = 0.558, t = 11.873, p = .000). Both news motives (MIN, β = 0.129, t = 2.178, p = .029, and MRN, β = 0.239, t = 4.031, p = .000) and CI (β = 0.599, t = 10.700, p = .000) significantly contributed towards SNS news consumption. In addition, news motives have positively determined PU, PE and ATT. Further, ATT positively predicted CI (β = 0.463, t = 8.433, p = .000), while perceptual factors (PU and PE) did not exert any impact on CI. The study also found mediating effects of news motives, perceptual-attitudinal factors and continuous intention. The findings of this study proved the utility of the integrated model in explaining SNS news consumption. Finally, the study presents its major contribution and theoretical implications as well as its key findings.